2013
DOI: 10.7575/aiac.alls.v.4n.2p.57
|View full text |Cite
|
Sign up to set email alerts
|

On Opinion and Persuasive Writing: Teaching English through Editorials

Abstract: Learning a language becomes easier when it is interpreted through certain contexts, of which, the sociocultural ones are the most important. Sociocultural interests, norms, customs and values are represented by the language as forms of "persuasive social acts". Media discourses can be cited as one example in this regard where language is an inevitable means of communicating opinions, making one's voice heard. Persuasive use makes media discourse interesting to explore in the classroom given the specificities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Newspaper have the power to develop the English language skills (Wolswinkel, 2008). In a study conducted by Afzal and Harun (2013), the researchers point out that the English lesson can be fun when the teachers and students discuss about the daily news published in the newspapers. They also reported that by exploring the news articles, students can learn on how the writer express their thoughts and how they manipulate the word knowledge.…”
Section: The Use Of Newspapers To Increase Vocabulary Knowledgementioning
confidence: 99%
“…Newspaper have the power to develop the English language skills (Wolswinkel, 2008). In a study conducted by Afzal and Harun (2013), the researchers point out that the English lesson can be fun when the teachers and students discuss about the daily news published in the newspapers. They also reported that by exploring the news articles, students can learn on how the writer express their thoughts and how they manipulate the word knowledge.…”
Section: The Use Of Newspapers To Increase Vocabulary Knowledgementioning
confidence: 99%
“…Since these features are embedded, advertisements are claimed to possess strong authentic materials that can trigger language learning. Another inquisition on authentic printed material specifically, editorials, conducted by Afzal and Harun (2013) reveals that editorials can probably aid in English language acquisition. To them, editorials can serve as patterns for writing activities.…”
Section: Authentic Materials In Varied Classificationsmentioning
confidence: 99%
“…The explicit feelings, technically called inscribed attitude, are the feelings that are clear enough to be seen without employing interpretation. Social semiotics has been studied in different discourse types including medical discourse (Adegbite&Odebunmi, 2006), gender discourse (Adegoju., 2011), political discourse (Ezeifeka, 2013;Oyeleye & Osisanwo, 2013), media discourse (Oha, 2006;Afzal & Harun, 2015;Adegoju, 2016). The literature on social semiotics in online discourse can be divided into two groups: empirical social semiotic research on visual signs (Matinec, 2003;Coulthard & Leeuwen, 2003;Grunschy, 2007;Mutowo, 2013;Kathryn, 2014), and empirical social semiotic research on linguistic signs (Oha, 2000;Adegbite & Odebunmi, 2006;Achi, 2008;Hua, 2008;Bennett, 2011;Yeibo, 2011).…”
Section: Social Semiotics In Discoursementioning
confidence: 99%